Relações entre bem-estar no trabalho e contexto de trabalho entre profissionais do setor de Tecnologia da Informação (TI) que trabalham remotamente - Silva, Mariana Isis Alves (2023)
Faced with constant transformations and modifications in the working lives of thousands of workers, driven by the COVID-19 pandemic, significant adaptations and reformulations in the work model were introduced, especially for Information Technology (IT) companies, which adopted remote work from permanently. There are few investigations with professionals in the IT area, which analyze the relationship between Work Context (WC) and Well-Being at Work (BET), such investigations have the potential to reformulate the health promotion of these professionals who work remotely. Thus, the objective of the research was: to analyze the relationships between well-being at work, the work context of professionals in the IT sector who work remotely. A convenience sample of 213 workers residing in Brazil, most of them men, was used. For data collection, multidimensional measures with evidence of empirical validation were selected. To investigate Work Context, the Work Context Scale-EACT measure was used, which is formed by the dimensions: working conditions, work organization and socio-professional relationships and to investigate Well-Being at Work, the BET measure was used, the which comprises the dimensions: positive affects, negative affects and professional and personal fulfillment. To analyze the results, descriptive statistics (frequency, mean, mode, median and standard deviation) and inferential statistics (Pearson Correlation and Linear Regression) were performed. The results show that the work context experienced by the surveyed professionals does not pose a serious risk to their health, the most prominent BET dimension was professional and personal fulfillment (M = 3.87, SD=0.73). The highest correlation between Work Context and BET occurred between the dimensions of work organization and negative affects (r=0.571; p<0.001). The CT variable predicts BET through the socio-professional relationships and work organization dimensions, highlighting that the socio-professional relationships dimension explains all the dimensions of BET. When comparing the data with the literature, it is observed that the work context is a predictor of well-being at work, that is, as professionals perceive how the organization has social relations, practices of interactions between peers, colleagues and managers are described, the greater the experience of well-being at work. The work made it possible to identify that there is a relationship between well-being at work and the work context experienced by the participants.